Interfacing live cells with nanocarbon substrates - Boey, Freddy Yin Chiang (2012)
Nanocarbon materials, including single-walled carbon nanotubes (SWCNTs) and graphene, promise various novel biomedical applications (e.g., nanoelectronic biosensing). In this Letter, we study the ability of SWCNT networks and reduced graphene oxide (rGO) films in interfacing several types of cells, such as neuroendocrine PC12 cells, oligodendroglia cells, and osteoblasts. It was found that rGO is biocompatible with all these cell types, whereas the SWCNT network is inhibitory to the proliferation, viability, and neuritegenesis of PC12 cells, and the proliferation of osteoblasts. These observations could be attributed to the distinct nanotopographic features of these two kinds of nanocarbon substrates.